2022
DOI: 10.3390/math11010207
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Neighborhood Granular Meanshift Clustering Algorithm

Abstract: The most popular algorithms used in unsupervised learning are clustering algorithms. Clustering algorithms are used to group samples into a number of classes or clusters based on the distances of the given sample features. Therefore, how to define the distance between samples is important for the clustering algorithm. Traditional clustering algorithms are generally based on the Mahalanobis distance and Minkowski distance, which have difficulty dealing with set-based data and uncertain nonlinear data. To solve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Regarding the fundamental Meanshift formulation described in Equations ( 1) and ( 2), there exists an issue: within the region of S h , every point contributes equally to x [17]. However, in reality, this contribution is related to the distance from x to each point.…”
Section: Meanshift Algorithm With Kernel Functionmentioning
confidence: 99%
“…Regarding the fundamental Meanshift formulation described in Equations ( 1) and ( 2), there exists an issue: within the region of S h , every point contributes equally to x [17]. However, in reality, this contribution is related to the distance from x to each point.…”
Section: Meanshift Algorithm With Kernel Functionmentioning
confidence: 99%
“…And then apply the DCFS model to predict a synthetic chaotic plus random time series and the Hang Seng Index of the Hong Kong stock market. Chen et al 26 found that the granular mean shift clustering algorithm has better clustering performance than traditional clustering algorithms, such as Kmeans, Gaussian mixture, etc. Sang et al 27 proposed a fuzzy rough feature selection method based on robust non-linear vague quantifier for ordinal classification.…”
Section: Introductionmentioning
confidence: 99%